Prospective and competitive intelligence in 2040 to promote programs innovation in Peru - Inche Mitma, Jorge Luis (2016)
This paper, resume a research that had as objetive build a future scenario to 2040 for programs that promote the innovation in Perú, inside the competitive intelligence. In order to achieve this goal, it considered a simple of 10 experts of differents organizations, and Through the implementation of interviews and surveys It was possible to identify 37 variables of the system, of which 23 were considered as keys, and with them built the future scenario. It’s a prospective research, therefore based on consultation with experts, the main difficulty encountered he resided in the availability of these; however, this was solved.